Pengembangan Media Pembelajaran Blended Learning Berbasis geo.ID Moodle Pada Materi Mitigasi Bencana Untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas XI SMA Negeri 1 Sukoharjo Tahun Ajar 2021/2022 - Bagas Annas Utomo; Singgih Prihadi; Gentur Adi Tjahjono (Universitas Sebelas Maret (UNS), 2022)
The purposes of this research were: (1) To know the student's needs for the development of geo.ID Learning Media based on blended learning (moodle), (2) To know the feasibility of geo.ID Learning Media based on blended learning (moodle), and (3) To know the effectiveness of geo.ID Learning Media based on blended learning (moodle) on Disaster Mitigation Materials to increase the outcomes of the students in XI grade SMA Negeri 1 Sukoharjo 2021/2022.The method used in this research was Research and Development (R&D). It was developing the learning media from Moodle Software into geo.ID. The research subject consists of material experts, media experts, and students. The method of collecting data were interviews, observations, documentation, and tests.The result of Research and Development are (1) The development of geo.ID Learning Media based on blended learning (moodle) adjusted with the student's needs which dominated by text learning style, learning experience or skills in using filter media, students were enthusiasts and agree with the development of media, blue colour visualization and Time New Roman font, (2) The development of geo.ID Learning Media based on blended learning (moodle) found much worthy for geography learning in XI Class SMA Negeri 1 Sukoharjo. It can be explained based on the results of the material expert's assessment which obtained 96% in the decent category, media experts obtained 86% in the decent category, individual trials and small group trials obtained 86% in the decent category. The data were collected using a Likert Scale. (3) The determination for used geo.ID learning media based on blended learning (moodle) was proven in increasing the learning outcomes on pretest-posttest which score was 76.3 while for the control class was 59.9. Keywords : Blended Learning Media, Moodle, geo.ID, Learning Outcome